Post-Modernism and the Social Sciences : Insights, Inroads, and Intrusions - Rosenau, Pauline Vaillancourt (Book collections on Project MUSE., 2001)
Post-modernism offers a revolutionary approach to the study of society: in questioning the validity of modern science and the notion of objective knowledge, this movement discards history, rejects humanism, and resists any truth claims. In this comprehensive assessment of post-modernism, Pauline Rosenau traces its origins in the humanities and describes how its key concepts are today being applied to, and are restructuring, the social sciences. Serving as neither an opponent nor an apologist for the movement, she cuts through post-modernism's often incomprehensible jargon in order to offer all.